COVID-19 Severity According to Age Groups in an Ecuadorian Hospital - Lina Espinoza Neri-Pire; Freddy Fernando Jumbo Salazar; Jenny Olivia Caicedo Rodríguez (Medisur)
Foundation: an increment in the COVID-19 severity has been observed with increasing age. Elderly people are more susceptible to suffer severity during SARS-CoV-2 infection due to weak immunity and other organ dysfunctions. Objective: to compare the COVID-19 severity in different age groups at the Ambato General Teaching Hospital, Ecuador. Method: a descriptive and cross-sectional study was carried out. The studied population was made up of 659 patients with COVID-19 treated at the Ambato General Teaching Hospital, at the end of 2021. The patients were separated into three age groups: young, middle-aged and older adults; the severity of COVID-19 was managed as mild, severe and serious. The Kruskal-Wallis test was used to determine differences in severity between age groups. Results: the COVID-19 severity tended to increase with age, as the group of older adults had the highest average range, followed by the group of middle-aged adults and, finally, by young adults. The Kruskal-Wallis H value was 238.522 with p < 0.01. Conclusions: in the patients studied, the COVID-19 severity varied according to age groups, with a greater result as age increased. This shows the need for care based on age and the need to draw up policies to quickly care for older adults diagnosed with COVID-19.